How Do Third-Party Funds Affect Loans? - Raharjo, Suko Basuki Wibowo Tunggul; Lestari, Etty Puji; Susilo, Adhi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The article aims to analyze the influence of third-party funds on the loan given to PT. Bank Rakyat Indonesia (Persero) Tbk Kanca Curup. The method used is multiple linear regression. Variables ? are the number of loans, savings, current accounts, and deposits. Research results show that the amount of funds raised, that is, current accounts, savings, and deposits in the future, positively and significantly influenced loans provided.? Deposits are the dominant factor that influences the size of the loan given. Thus, banks should pay more attention to the existence of third-party funds because this will affect their banking performance. Concrete steps that can be taken to increase the collection of third-party funds are improving services and introducing various types of banking service products with appropriate interest rates.